Exergy-Based Life Cycle Assessment of Buildings: Case Studies - Martin Nwodo (MDPI AG, 2021)
The relevance of exergy to the life cycle assessment (LCA) of buildings has been studied regarding its potential to solve certain challenges in LCA, such as the characterization and valuation, accuracy of resource use, and interpretation and comparison of results. However, this potential has not been properly investigated using case studies. This study develops an exergy-based LCA method and applies it to three case-study buildings to explore its benefits. The results provide evidence that the theoretical benefits of exergy-based LCA as against a conventional LCA can be achieved. These include characterization and valuation benefits, accuracy, and enabling the comparison of environmental impacts. With the results of the exergy-based LCA method in standard metrics, there is now a mechanism for the competitive benchmarking of building sustainability assessments. It is concluded that the exergy-based life cycle assessment method has the potential to solve the characterization and valuation problems in the conventional life-cycle assessment of buildings, with local and global significance.